Myocardial serotonin exchange: negligible uptake by capillary endothelium - MOFFETT, T. C. (1988)
The extraction of serotonin from the blood during transorgan passage through the heart was studied using Langendorff-perfused rabbit hearts. Outflow dilution curves of (131)I- or (125)I-labeled albumin, [(14)C]sucrose, and [(3)H]serotonin injected simultaneously into the inflow were fitted with an axially distributed blood-tissue exchange model to examine the extraction process. The model fits of the albumin and sucrose outflow dilution curves were used to define flow heterogeneity, intravascular dispersion, capillary permeability, and the volume of the interstitial space, which reduced the degrees of freedom in fitting the model to the serotonin curves. Serotonin extractions, measured against albumin, during single transcapillary passage, ranged from 24 to 64%. The ratio of the capillary permeability-surface area products for serotonin and sucrose, based on the maximum instantaneous extraction, was 1.37 ± 0.2 (n = 18), very close to the predicted value of 1.39, the ratio of free diffusion coefficients calculated from the molecular weights. This result shows that the observed uptake of serotonin can be accounted for solely on the basis of diffusion between endothelial cells into the interstitial space. Thus it appears that the permeability of the luminal surface of the endothelial cell is negligible in comparison to diffusion through the clefts between endothelial cells. In 18 sets of dilution curves, with and without receptor and transport blockers or competitors (ketanserin, desipramine, imipramine, serotonin), the extractions and estimates of the capillary permeability-surface area product were not reduced, nor were the volumes of distribution. The apparent absence of transporters and receptors in rabbit myocardial capillary endothelium contrasts with their known abundance in the pulmonary vasculature.